Determinants of flexible work arrangements - Miruna Sarbu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Flexible work arrangements such as allowing employees to work at home are used in firms, especially since information and communication technologies have become so widespread. Using individual-level data from 10,884 German employees, this paper analyses the determinants of working at home as a form of flexible work arrangements. The analysis is based on descriptive analyses and a discrete choice model using a probit estimation approach. The results reveal that men have a higher probability to work at home but women are more likely to work at home intensively. Education, tenure and the use of computers increase the probability of working at home while firm size and a young age of employees reduce it. Having children less than six years old, overtime and work time have a positive impact on both working at home and on working at home intensively.
urn:nbn:de:bsz:180-madoc-367037
Keywords: J01; J10; J20; 330; work at home; telecommuting; home office; workplace organisation